ENHANCING THE LEARNING OUTCOMES IN ENGLISH COURSE MATERIAL WITH PASSIVE VOICE THROUGH THE APPLICATION OF THE WINDOW-SHOPPING LEARNING MODEL - Sumiyati Sumiyati (Intensive Journal, 2022)
This research aims to improve the learning outcomes of English Subject Subjects with Passive Voice by applying the Window-shopping learning model to class IX E students of SMP Negeri 5 Banjarmasin Odd Semesters in the 2021/2022 Academic Year. It was in two cycles: planning and implementing the action, observing (observation), and reflection. Data were collected through observation, tests, and documentation and then analyzed descriptively by percentage. The results showed an increase in English learning outcomes for passive voice in Class IXE students at SMP Negeri 5 Banjarmasin through the window-shopping learning model. It can be seen from the increase in student learning outcomes from the pre-cycle, first, and second cycles. Its average value in the pre-cycle was 63.4, increased to 68.3 in the first cycle, and increased again in the second cycle to 74.